2003
DOI: 10.1149/1.1606687
|View full text |Cite
|
Sign up to set email alerts
|

Sn-Ag Solder Bump Formation for Flip-Chip Bonding by Electroplating

Abstract: Pb-free Sn-Ag alloy solder bumps for flip-chip bonding were formed by electroplating with the aid of a photolithography. Pyrophosphate-iodide baths were used for the plating bath. Smooth, fine-grained Sn-Ag alloy films were obtained using a bath containing both polyethylene glycol ͑mean molecular weight 600, PEG600͒ and formaldehyde ͑HCHO͒ additives. Sn-Ag alloy films with near eutectic compositions ͑Sn-3.8 atom % Ag͒ were obtained under both galvanostatic and potentiostatic conditions. All of the Sn-Ag alloy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Many authors studied the electrochemical behaviour of pure tin [3][4][5][6][7][8][9] and pure silver [10][11][12] in different media. But few studies are done on tin-silver alloys [13][14][15][16][17][18][19][20][21][22]. The behaviour of some alloys in fluoride solutions was studied by some authors [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Many authors studied the electrochemical behaviour of pure tin [3][4][5][6][7][8][9] and pure silver [10][11][12] in different media. But few studies are done on tin-silver alloys [13][14][15][16][17][18][19][20][21][22]. The behaviour of some alloys in fluoride solutions was studied by some authors [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…As a bumping method, electroplating is considered to be a suitable process due to its efficiency in fabricating smaller sized and narrower pitched bumps. 20) Electroplating processes for solder bumps generally employ a photo-resist-mold (PRM) on a Si wafer [20][21][22][23][24][25][26] to confine the cathode surface area and control the shape of the deposits. However, applying a PRM requires a series of processes; PR coating, ultra-violet (UV) exposure, development and PR removal, which involve extra time and cost.…”
Section: Introductionmentioning
confidence: 99%
“…In this line of research, tin has found numerous uses as the active ingredient of the existing solders since it wets and alloys with a wide range of commonly used base metals. Among the binary tin alloys which have been studied as promising candidates are tin-copper [3][4][5][6], tin-aluminum, [7] and tinsilver [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%